A Retrospective Study Comparison Between Stenting and Standardized Medical Treatment for Intracranial Vertebrobasilar Stenosis in a Real-World Chinese Cohort - Li, Guanzeng; Yan, Peng; Zhao, Yuanyuan; Li, Shan; Xue, Yuan; Xiang, Yuanyuan; Liu, Xiaohui; Li, Jifeng; Sun, Qinjian (Frontiers in Neurology, 2021)
Background: To date, there has been no consensus regarding the benefits of percutaneous transluminal angioplasty and stenting (PTAS) vs. those of standardized medical treatment (SMT) for patients with symptomatic intracranial vertebrobasilar stenosis (IVBS). The purpose of this retrospective study was to compare the effects of PTAS or SMT on symptomatic IVBS in a real-world Chinese population. Methods: We included 238 patients with ischemic stroke caused by IVBS stenosis who were admitted to Shandong Provincial Hospital Affiliated to Shandong University between September 2012 and May 2018; 62 of these patients were treated with SMT and 176 underwent PTAS. Ischemic stroke in the territory of the responsible artery, hemorrhage, and death within 1 year were recorded as primary endpoints. Secondary endpoints included assessment of stroke severity and the incidence of re-stenosis. The primary endpoint rates were compared between the PTAS and SMT groups at 7 days, 1, 6 months, and 1 year. Results: In the PTAS group, the success rate of stent placement was 98.9%. During the entire trial, except for 7 days, the SMT group had a higher frequency of primary endpoint events than did the PTAS group. The primary endpoint was 17.7% (11/62) vs. 8.6% (15/174) at 1 month (p = 0.049), 29% (18/62) vs. 14.4% (25/174) at 6 months (p = 0.01), and 32.2% (20/62) vs. 17.2% (30/174) at 1 year (p = 0.013). The restenosis rate of the target lesion was 13.8%; 60% were symptomatic restenosis and 40% were asymptomatic restenosis. The rate of severe stroke at 1 year after PTAS was 0%, while that in the SMT group was 9.7%. Conclusions: In a real-world Chinese cohort, PTAS for patients might be superior to SMT, and provide better long-term neurological function recovery and lower disability rate.